Durian Farmland Valuation in Malaysia - Mohamad Sufawi, Ezril Fairez; Omar, Abdul Jalil (Research in Management of Technology and Business, 2025)
This study discusses the valuation of durian agricultural, by focusing on the factors that influence the value of land and the challenges in the valuation process. The main factors studied include the age of the tree, type of tree, landform, location, area conditions, and the existence of buildings and infrastructure facilities that influence the market value of durian agricultural land, especially the high-value Musang King durian variety. This study also identified the main challenges in the valuation process, such as outdated area information, difficulty in accessing the interior, environmental factors, and the valuation process, which is technical and requires high expertise. The study data was obtained through a qualitative approach with interviews with property valuers from the private and government sectors as well as a literature review from journal articles and related reference sources. Data analysis shows that the location factor, tree type, and tree age are the main elements that influence the market value of durian agricultural land, while the lack of data and the complex valuation process are the main challenges. This study recommends an increase in the use of systematic data recording including financial inflow and outflow in valuation approach to ensure accuracy, fairness, and effectiveness in the valuation of agricultural land in the area. It is hoped that these findings will be a useful guide for property valuers, landowners, and stakeholders in the agricultural property sector.